STUDY OF METAL CONTAMINANT LEVEL IN THE MAHAKAM DELTA: SEDIMENT AND DISSOLVED METAL PERSPECTIVES - Fitri Budiyanto; Lestari . (JOURNAL OF COASTAL DEVELOPMENT, 2013)
The Mahakam Delta in East Kalimantan contains large number of natural resources specially hydrocarbon sources. Anthropogenic activities have influenced this ecosystem for many years. The aims of this work were to find out dissolved metal and metals in sediment distribution in this area and to find out contaminant level based on allowable guidelines. Twenty nine stations were sampled within the delta and metal content analyses, both in sediment and water column, were established for Cd, Cu, Ni, Pb and Zn. Sediment analyses were conducted using US EPA 3050B method and dissolved metals analyses were conducted using Back Extraction method. Cd, Cu, Ni, Pb and Zn in sediment had 0.07 mg/kg dw, 18.64 mg/kg dw, 35.62 mg/kg dw, 10.56 mg/kg dw and 74.95 mg/kg dw in maximum concentration respectively. Whereas dissolved Cd, Cu, Ni, Pb and Zn had 0.001 mg/l; 0.003 mg/l; 0.003 mg/l; 0.013 mg/l and 0.003 mg/l in maximum concentration respectively. Based on allowable guidelines, metals contaminat levels, both in sediment and water column, were below permitted value.